Tips Berdakwah Ala Generasi Millenial di Era 4.0 - Ayu Marlia Hikmah; Rama Wijawa Kusuma Wardani; Alex Chandra; Muhammad Yamin (STAI Bumi Silampari, 2021)
Millennials who rely on technology and still use ipads, smartphones, TVs, and so on. Every day makes social media a very important part of social connections. They spend more time a day with digital technology devices, as well as a variety of apps than they spend with their families, because of too much surfing in cyberspace, millennials often neglect the obligation to worship. The research method in this study is qualititative research method. Qualitative approach focuses on the general principles underlying the realization of a meaning of social symptoms in society. The object of analysis in qualitative approach is the meaning of social and cultural symptoms by using the culture of the community concerned to obtain an overview of a particular category. The study objectives of qualitative approach are patterns that apply as general principles that live in society.These symptoms are seen from a stand-alone unit in a round and complete unity. So qualitative approach is often referred to as holistic approach to a social symptom. First, preaching through psychological approach, psychological approach is very important to know which methods and processes of acceptance will be taken against the object of preaching through. Second, rhetorical approach, namely by conveying messages and advice through writing or directly such as questions and discussions preaching through examples of conscientiousness. Teenagers in today''s millennial era love to imitate someone they admire. Tips on preaching to millennials in the 4.1 era, namely by using psychological approaches, rhetorical approaches, through setting a good example, and through social media.